Internalization of Moral Education Values in the Tarbawi Hadith and Its Relevance to the Formation of Social Morals - Fatoni, Ahmad; Bagaskara, Figo Rangga; Hadi, Ahmad Ikhlas Muhtar (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2025)
The purpose of this research is to identify the values of moral education in the Tarbawi hadiths, describe the process of internalizing moral values in everyday life, and analyze the relevance of the values of the Tarbawi hadiths to the formation of social morals in society. This research uses a descriptive qualitative approach. The main data source in this research is the Tarbawi hadith contained in authentic hadith books such as Sahih al-Bukhari, Sahih Muslim, and al-Arba'in al-Nawawiyah. Apart from that, secondary sources were obtained from literature, books, journal articles, and previous research that discussed moral education in Islam and its implementation in education. The collected data will be analyzed using content analysis and thematic analysis. The research results state that the process of internalizing these moral values can be done through habituation, role models, giving advice, and a supportive environment. The internality of these moral values is very important for creating individuals with integrity and social responsibility. In addition, the values contained in the hadiths of Tarbawi also have great relevance to forming social morals by fostering concern, solidarity, justice, tolerance, and reducing conflict in society. The instillation and practice of these values will produce a better, more harmonious, and more compassionate society.